On-line database of photometric observations of magnetic chemically peculiar stars and its exploitations - Janik, J.; Mikulasek, Z.; Zverko, J.; Ziznovský, J. (Известия Крымской астрофизической обсерватории, 2008)
On-line Database of Photometric Observations of Magnetic CP Stars established in 2005 contains now 120 thousands individual observations of 110 mCP stars. It is being regularly refilled by new data; presently they have been added by ASAS2/ASAS3 measurements of database stars. We have improved database scripts allowing calculating and plotting phase curves for individual stars. Now we are preparing the interface between database and scripts for advanced data processing. Investigators interested in detailed study of database stars are welcome.